Mga kagamitang panturo na gumagamit ng apat na dimensyon ng pag-unawa sa pagbasa sa pagtuturo ng mga piling kuwentong-bayan ng Cagayan sa mga estudyanteng Ibanag sa ikaanim na grado - Quinan, Pilar Alfonso 1932- (1975)
This study includes twelve folktales of Cagayan that have been translated from a book "The Cayana Series" vol. III FOLKTALES. In choosing the stories for translation, the writer took into consideration the child who will read these stories - the vocabulary of the stories, whether the stories are within their experiences, and whether the stories appeal to their interest according to their sex. Several abilities may be developed through each dimension in each story in order to make the learning of reading interesting for children.
Thesis (M.A.T.)--University of the Philippines, Quezon City
Keywords: Reading (Elementary) -- Philippines -- Cagayan; Reading -- Aids and devices. -- Philippines -- Cagayan